2015
DOI: 10.1556/032.65.2015.3.5
|View full text |Cite
|
Sign up to set email alerts
|

What drives China’s outward direct investment?

Abstract: This study examines the determinants of China's outward direct investment (ODI) between 2003 and 2009. We fi rst analyse the structure and dynamics of ODI. We propose three testable hypotheses including technology sourcing, resource seeking, and political linkage. Various estimates show that technology sourcing is supported moderately, whereas resource seeking serves one of primary driving forces. Crucially, the motive of political linkage is signifi cantly related to ODI and it is particularly relevant to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…Studies by Desbordes and Wei [14], Oláh et al [24], Sadaf et al [25], Forssbaeck and Oxelheim [26], Yang et al [5], and Yoo and Reimann [6] explain the reason for internationalization in terms of outward foreign investment from the country by focusing on the real determinants of the international activities of firms. Athreye and Godley [27] and Desbordes and Wei [14] identify that without real advantages, such as economic prosperity and economic development, internationalization cannot be successful.…”
Section: Financial Availability and Internationalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Desbordes and Wei [14], Oláh et al [24], Sadaf et al [25], Forssbaeck and Oxelheim [26], Yang et al [5], and Yoo and Reimann [6] explain the reason for internationalization in terms of outward foreign investment from the country by focusing on the real determinants of the international activities of firms. Athreye and Godley [27] and Desbordes and Wei [14] identify that without real advantages, such as economic prosperity and economic development, internationalization cannot be successful.…”
Section: Financial Availability and Internationalizationmentioning
confidence: 99%
“…The increasing internationalization of emerging firms is receiving notable attention in the literature of International business [1][2][3][4][5][6]. Studies reveal that internationalization takes place with an overall increased investment pattern by firms because of growing economic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Ross (2015) found that natural resources’ access, regulatory environment and quality of infrastructure in the host countries are the main determinants of China’s OFDI in Africa; Elshamy (2015) reported similar findings for the Chinese FDI in Egypt; the author identified that China’s liberalized policies had a significant positive impact on its FDI in Egypt. However, contrary to the FDI theory, Yang et al (2015) indicated that China had a tendency of investing in developing economies having a great political risk; the authors further reported that seeking political relationship and accessing natural resources are among the prime motives of China’s investment in such economies. Miniesy and Elish (2017) also described that China seeks resources of its OFDI-receiving nations, and weak governance of the host countries is a significant determinant of its OFDI.…”
Section: Literature Reviewmentioning
confidence: 82%
“…The geographic proximity, macroeconomic conditions, institutional environment, and cultural familiarity in host countries are also influential in MNCs' investment decisions (Voss, 2011). Based on these theoretical explanations, a great amount of literature has explored the linkages between conventional FDI theories and Chinese firms' motives for OFDI (Cheung & Qian, 2009; Yang, Cheng, & Lin, 2015). Dunning's eclectic paradigm was widely employed to investigate Chinese firms' OFDI motives, which include ownership, location, and internalization advantages (Hurst, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several other variables, such as macroeconomic conditions, trade relations, and political stability in host countries, are used to categorize China's diversified OFDI motives (Bhaumik & Co, 2011;Ramasamy & Yeung, 2020;Yang et al, 2015). This article, however, argues that China's OFDI represents a different type of investment that cannot be fully explained by the conventional FDI theories.…”
mentioning
confidence: 98%